Exploratory analysis of the “all-inclusive” system: Implications for economic indices of tourism activity after the Covid-19 economic crisis - ZRELLI, Imen; BOUTHAINA, Fekih (The journal of contemporary issues in business and government, 2021)
The purpose of this article is to study the booking structure, cost and profitability of accommodation companies that implement an AIS (AIS), especially after the economic crisis linked to Covid-19. To this end, the managers of accommodation companies located in one of the largest Tunisian seaside resorts were interviewed and the results were evaluated in a comparative manner with their structure before the AIS. This research is based on tow parts. The first is an internal analysis of the figures before and after the application of AIS. The second deals with face-to-face interviews with the managers of the various services of hosting companies. The approach of this research is both qualitative and quantitative. This research attempted to explain the reasons why the all-inclusive system was preferred by accommodation companies in the Hammamet region in Tunisia, especially after the economic crisis linked to Covid-19. The reasons for customer dissatisfaction are linked to the poverty of the system in cultural terms. The general opinion of the leaders was that companies preferred the AIS because of competitive pressure rather than for profitability reasons, especially after the economic crisis linked to Covid-19.